Laporan Kasus Kanker Endometrium Tipe Sekretori: Kasus Jarang - Subandi Subandi (Journal of Issues in Midwifery, 2023)
Endometrial cancer is the most common gynecological cancer in developed countries, second most in poor countries and developing countries after cervical cancer. Most endometrial cancer patients come with complaints of bleeding and come at an early stage. It’s important to make the right diagnosis to determine the appropriate treatment. Treatment depends on the stage determined by surgery. After surgery, the patient’s risk was classified as low, moderate, or high risk. This risk is determined by stage, cell type, differentiation, involvement of blood vessels and lymph vessels. From these risk factors, it is determined whether or not additional postoperative therapy is needed in the form of radiation or chemotherapy. Secretory type of endometrial cancer is a rare endometrial malignancy. This case’s population is 1-2% of all endometrial cancer. Histologically, this type of cancer belongs to type one. We report a secretory type of endometrial cancer case in a 41-year-old woman with a complaint of irregular menstruation, and a total hysterectomy, bilateral salpingo oophorectomy, bilateral pelvic lymphadenectomy and para-aortic lymphadenectomy was done. Histologically, secretory carcinoma must be separated from carcinoma clear cell to determine the prognosis.